Fatigue life prediction of basalt-carbon hybrid composite for wind turbine rotor blades - MENGAL, ALI NAWAZ (2016)
Modem wind turbine blade sizes are increasing, and the driving motivation behind this is to increase the efficiency and energy output per unit rotor area. However, due to the increase in size, the material selection for wind turbine has become critical and complex.